An improvement in LQR controller design for TLIP system via model order reduction - Juneja M.; Nagar S.K. (My University, 2025)
The Model order reduction is crucial for analysing complex order systems. The primary objective of reduced order modelling aims at obtaining the lower order equivalent which gives sufficient representation of its higher order counterpart while preserving the key features of the system. The controller designed for such reduced order systems is simpler in terms of its dimensionality and controller parameters involved as compared to the same for higher order system. This paper focusses on using Particle Swarm Optimization (PSO) reduced model for comparing the end results of LQR controller which has been designed for both higher and lower order equivalents of Triple Link Inverted Pendulum (TLIP) system. The reduced order model uses a controller which is simplified and gives better performance due to decreased effect of certain control parameters on the overall controller design. © International Research Publication House.